Cadeia produtiva de atum (Thunnus spp.) em Itarema, Ceará - Freitas, Lília Freire (2018)
It was intended, with this work, obtain relevant information about the several sectors of the tuna fish and tuna-like productive chain at the city of Itarema. In addition to the productive chain, a brief historic of this fishing activity at the comunity has been drawn up, as well as a financial subtle analysis of fishery. For the construction of the history was used field experience, which focused on the collective construction of dialogue. The design of the production chain was based on documentary research, bibliographical research and field experience. The financial analysis was based on the methodology of Santos et al. (2011), which took into account the effective operating cost, total cost, gross revenue, effective operating profit and profitability index. Tuna fishing began in 2013, when a local businessman became aware of the success and expansion of the fishery in Rio Grande do Norte. Currently this is the main fishing activity carried out in the municipality, with more than 80 vessels operating in the region. The productive chain consists of five sectors: support and inputs, production, processing, distribution and consumption. The total production of tunas in the community of Porto dos Barcos in 2016 was 509.3 tons, in which 95% were tuna of the species Thunnus albacares and Thunnus obesus, 3.85% corresponded to the production of the beautiful striped and only 1.15% of the production was of golden (Coryphaena hippurus). In the year 2017, production was 570.1 tons, 87.7% of which were tuna, 11.72% beautiful striped and only 0.58% gold. The Operating Profit on sales of fish in 2016 was R $ 713,876.16 and a profitability index of 26.76%. In 2017, operating profit was R $ 806,981.18, with a profitability index of 27.17% in relation to gross revenue and referring to a production of 570 tons of fish. Tuna fishing is considered the most important in the world, and if it is an international waters resource, it is necessary to monitor the development of this activity in the region once it is in exponential expansion.